UMA FENOMENOLOGIA AUTOBIOGRÁFICA E SUA CONTRIBUIÇÃO PARA A COMPREENSÃO DO SER PEDAGOGA PARA ALÉM DE ESPAÇOS-TEMPOS PRÉ-DETERMINADOS - Almeida, Isabel Cristina Dose Lage de (2020)
This is a research of Professional Master s Degree in Education with the objective of carrying out a phenomenological-autobiographical study on what it is (how it is) to be a beginner educator experiencing this process in the age group of 50 years. In ter